Ferroportin 3 is a dual‐targeted mitochondrial/chloroplast iron exporter necessary for iron homeostasis in Arabidopsis - Kim, Leah J.; Tsuyuki, Kaitlyn M.; Hu, Fengling; Park, Emily Y.; Zhang, Jingwen; Iraheta, Jennifer G.; Chia, Ju‐Chen; Huang, Rong; Tucker, Avery E.; Clyne, Madeline; Castellano, Claire; Kim, Angie; et al. (The Plant journal : for cell and molecular biology, 2021)
Summary Mitochondria and chloroplasts are organelles with high iron demand that are particularly susceptible to iron‐induced oxidative stress. Despite the necessity of strict iron regulation in these organelles, much remains unknown about mitochondrial and chloroplast iron transport in plants. Here, we propose that Arabidopsis ferroportin 3 (FPN3) is an iron exporter that is dual‐targeted to mitochondria and chloroplasts. FPN3 is expressed in shoots, regardless of iron conditions, but its transcripts accumulate under iron deficiency in roots. fpn3 mutants cannot grow as well as the wild type under iron‐deficient conditions and their shoot iron levels are lower compared with the wild type. Analyses of iron homeostasis gene expression in fpn3 mutants and inductively coupled plasma mass spectrometry (ICP‐MS) measurements show that iron levels in the mitochondria and chloroplasts are increased relative to the wild type, consistent with the proposed role of FPN3 as a mitochondrial/plastid iron exporter. In iron‐deficient fpn3 mutants, abnormal mitochondrial ultrastructure was observed, whereas chloroplast ultrastructure was not affected, implying that FPN3 plays a critical role in the mitochondria. Overall, our study suggests that FPN3 is essential for optimal iron homeostasis. Significance Statement Iron homeostasis must be tightly controlled in the mitochondria and chloroplasts, but iron trafficking in these organelles is not fully understood. Our work suggests that FPN3/IREG3 is an iron exporter required for maintaining proper iron levels in mitochondria and chloroplasts. Furthermore, FPN3 is necessary for optimal growth and normal mitochondrial ultrastructure under iron deficiency. This study reveals the physiological role of FPN3 and advances our understanding of iron regulation in mitochondria and chloroplasts.